After Eden church fathers and rabbis on Genesis 3:16-21 - Reuling, Hanneke (Leiden [u.a.] Brill, 2006)
The Spirit, the flesh, and Genesis three -- The versions of Genesis 3:16-21 -- Adam, Eve, and the hidden meaning of Scripture -- Beyond paradise : John Chrysostom preaching on the primordial ordeal -- Genesis and the stain of sin : spiritual, literal and dogmatic interpretation in the writings of Augustine of Hippo -- Eden as paradigm? : Genesis Rabbah's collection of interpretations -- Avot de Rabbi Nathan : human origins and the rabbinic framework -- After Eden
Includes bibliographical references (p. [343] - 357) and index
Teilw. zugl.: Utrecht, Univ., Diss., 2004
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- O.T -- Genesis III, 16-21 -- Criticism, interpretation, etc; Hochschulschrift